Concordant Parent–Child Reports of Anxiety Predict Impairment in Youth With Functional Abdominal Pain. Issue 3 (March 2015) - Cunningham, Natoshia R.; Cohen, Mitchell B.; Farrell, Michael K.; Mezoff, Adam G.; Lynch-Jordan, Anne; Kashikar-Zuck, Susmita
ABSTRACT: Background: Functional abdominal pain (FAP) is associated with significant anxiety and impairment. Prior investigations of child anxiety in youth with FAP are generally limited by small sample sizes, based on child report, and use lengthy diagnostic tools. It is unknown whether a brief anxiety-screening tool is feasible, whether parent and child reports of anxiety are congruent, and whether parent and child agreement of child anxiety corresponds to increased impairment. The purpose of this investigation was to examine anxiety characteristics in youth with FAP using parent and child reports. Parent–child agreement of child anxiety symptoms was examined in relation to pain and disability. Methods: One hundred patients with FAP (8–18 years of age) recruited from pediatric gastroenterology clinics completed measures of pain intensity (Numeric Rating Scale) and disability (Functional Disability Inventory). Patients and caregivers both completed a measure of child anxiety characteristics (Screen for Child Anxiety and Related Disorders). Results: Clinically significant anxiety symptoms were more commonly reported by youth (54%) than their parents (30%). Panic/somatic symptoms, generalized anxiety, and separation anxiety were most commonly endorsed by patients, whereas generalized anxiety, separation anxiety, and school avoidance were most commonly reported by parents. The majority (65%) of parents and children agreed on the presence (26%) or absence (39%) of clinically significant anxiety. Parent–child agreement of clinically significant anxiety was related to increased impairment. Conclusions: A brief screening instrument of parent and child reports of anxiety can provide clinically relevant information for comprehensive treatment planning in children with FAP.